Sosialisasi Karya Tulis Ilmiah Bagi Siswa SMA Negeri 1 Kuala Kabupaten Nagan Raya - Sopar, Sopar; Yana, Rahmah Husna; Abdillah, Ligar; Juraida, Irma; Yulianda, Riki (Medan Resource Center, 2024)
Community service activities with the theme of socializing scientific writing for students at SMA Negeri 1 Kuala Nagan Raya Regency aim to increase students' interest in writing because the aim of writing is no longer just stringing words together, but demands more complex abilities. The approach method used in this service is through outreach to students of SMA Negeri 1 Kuala, Nagan Raya Regency, Aceh Province, totaling 30 (thirty) people. The planned activities are in the form of socialization which will later be followed by questions and answers, discussions and writing practice for participants. Based on the results obtained in the KTI outreach to SMA Negeri 1 Kuala, Nagan Raya Regency, Aceh Province, it can be explained that the students are able to understand and understand the importance of writing as scientific work in school. The growth and development of students' interest and talent in writing at SMA Negeri 1 Kuala, Nagan Raya Regency, Aceh Province towards scientific writing which is expected to be able to grow and develop student achievements together.